MANDIBULAR THIRD MOLAR ANGULATION IN EXTRACTION AND NON EXTRACTION ORTHODONTIC CASES - Ahmed, Imtiaz; Erum, Gul -e-; Kumar, Naresh (Journal of Ayub Medical College Abbottabad, 2011)
Background: The purpose of this study is to determine the angulation of mandibular third molar in orthodontic cases which are planned for extraction and non extraction. Methods: This is a cross-sectional descriptive study in which pre-treatment panoramic radiographs of 49 patients, age range 11-26 years were taken from the OPD of Department of Orthodontics, Dr. Ishrat- ul -Ebad Khan Institute of Oral and Health Sciences (DIKIOHS), Dow University of Health Sciences. The angles between the long axis of the second and third molars were measured. Descriptive statistics were applied. Mann-Whitney U-test was used for intergroup comparison extraction and non extraction cases. Results: This study consists of 49 patients with mean age of 17.94 years. Over all result concluded that mandibular third molar angulations were from 8-94º in extraction cases and 10-73º in non extraction cases. However, the pre-treatment 3rd molar angulation differences in extraction and non extraction cases were statistically insignificant with p-value >0.05. Conclusions: This study evaluates third molar angulations in pre-treatment cases, the differences in angulation were like other morphological differences but changes in angulation after treatment may or may not be related to extractions. Keywords: Third molar angulation, extraction and non extraction orthodontic cases